Sharīʿah governance and agency dynamics of Islamic banking operations in the Kingdom of Saudi Arabia - Abul Hassan; M. Sadiq Sohail; Md Mahfuzur Rahaman Munshi (ISRA International Journal of Islamic Finance, 2022)
Purpose - This study aims to investigate and point out the variations of agency theory in the context of Sharīʿah governance in Islamic banking operations in the Kingdom of Saudi Arabia (KSA). Design/methodology/approach - The study followed the approach of quantitative Corporate Governance Index (CGI) by computing the Gov-index (Gompers et al., 2003) and the Gov-score (Brown and Caylor, 2004; Saffieddine, 2009) to examine corporate governance (CG) issues using primary as well as secondary data. The primary data was generated from three full-fledged Islamic banks (IBs) and nine traditional banks with Islamic banking wings, all operating in the KSA. The approach was to provide an insight into the agency structure in the context of Islamic banking, which may lead to a trade-off between the conformity of Sharīʿah (Islamic law) rules and processes followed in safeguarding the rights of investors. Findings - The majority of the Islamic banking services that are surveyed in this study acknowledge the significance of Sharīʿah governance and have implemented the fundamental methods, in conformity with this system. Certain flaws in Sharīʿah governance principles pertaining to audit, control and transparency are reported. Practical implications - The research outcomes will be invaluable to IBs aiming to improve existing SG practices. It also has implications for IB managers to design strategies while complying with regulations and to protect the interests of all investors without breaching the ethics of Sharīʿah. Originality/value - This paper adds original value to the body of knowledge on agency relationship by analysing the dynamics of agency theory in the unique and complex context of Sharīʿah governance of IBs or those offering Islamic products in the KSA. The results can be used as a valuable feedback for improvement of Sharīʿah governance in the banking system in the KSA and the Gulf region at large.
Keywords: 330; Agency dynamics; Board of directors; Corporate governance; Financial reporting; Islamic banking; Shariah governance